An Overview of Continuing Medical Education/Continuing Professional Development Systems in Latin America: A Mixed Methods Assessment - Lawrence Sherman; Ricardo Leon-Borquez; Mildred Lopez; Kathy Chappell (Taylor & Francis Group, 2024)
The aims of this regional assessment of continuing medical education (CME)/continuing professional development (CPD) systems in Latin America were to describe the current requirements, if any, for physicians to engage in CME/CPD, explore perceptions of national CME/CPD systems from in-country subject matter experts (SMEs), to describe the perceptions of interprofessional continuing education (IPCE) and independent CME/CPD from in-country physicians and to provide recommendations that may be adopted by organisations/countries to improve the quality and effectiveness of their current CME/CPD systems and better meet their learners' needs. An assessment of 11 CME/CPD systems in Latin America was conducted using a mixed-methods approach that included 1:1 interviews with in-country SMEs and an electronic survey capturing qualitative and quantitative data from practicing in-country physicians. This assessment reflected countries with CME/CPD systems that are in various stages of maturity. Only three countries have systems that are self-regulated by the profession, several systems lack independence from pharmaceutical influence, and educational activities are described more in terms of traditional CME/CPD as compared to education focused on individual or team gaps or population health care needs. There was little description of incorporating learner self-assessment and evaluation of change and little focus on interprofessional education. This mixed-method assessment of 11 Latin American countries demonstrated CME/CPD systems that are developing in maturity. Participation was often voluntary, and there was relatively little regulation. Physicians overall have been resistant to regulation and have preferred to use a voluntary, incentive-based model. There was a relatively high degree of influence by the pharmaceutical industry. Affordability and access remain challenges. There is an opportunity to better tie country/population health outcomes to CME/CPD, implement interprofessional continuing education, increase faculty skills and learner engagement, and increase funding and access across geographic regions.